LDL receptors, caveolae and cholesterol in endothelial dysfunction: oxLDLs accomplices or victims?. (18th October 2020) - Luchetti, Francesca; Crinelli, Rita; Nasoni, Maria Gemma; Benedetti, Serena; Palma, Francesco; Fraternale, Alessandra; Iuliano, Luigi
Abstract : Oxidized LDLs (oxLDLs) and oxysterols play a key role in endothelial dysfunction and the development of atherosclerosis. The loss of vascular endothelium function negatively impacts vasomotion, cell growth, adhesiveness and barrier functions. While for some of these disturbances, a reasonable explanation can be provided from a mechanistic standpoint, for many others, the molecular mediators that are involved are unknown. Caveolae, specific plasma membrane domains, have recently emerged as targets and mediators of oxLDL‐induced endothelial dysfunction. Caveolae and their associated protein caveolin‐1 (Cav‐1) are involved in oxLDLs/LDLs transcytosis, mainly through the scavenger receptor class B type 1 (SR‐B1 or SCARB1). In contrast, oxLDLs endocytosis is mediated by the lectin‐like oxidized LDL receptor 1 (LOX‐1), whose activity depends on an intact caveolae system. In addition, LOX‐1 regulates the expression of Cav‐1 and vice versa. On the other hand, oxLDLs may affect cholesterol plasma membrane content/distribution thus influencing caveolae architecture, Cav‐1 localization and the associated signalling. Overall, the evidence indicate that caveolae have both active and passive roles in oxLDL‐induced endothelial cell dysfunction. First, as mediators of lipid uptake and transfer in the subendothelial space and, later, as targets of changes in composition/dynamics of plasma membrane lipids resulting from increased levels of circulating oxLDLs. Gaining a better understanding of how oxLDLs interact with endothelial cells and modulate caveolae‐mediated signalling pathways, leading to endothelial dysfunction, is crucial to find new targets for intervention to tackle atherosclerosis and the related clinical entities. LINKED ARTICLES: This article is part of a themed issue on Oxysterols, Lifelong Health and Therapeutics. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v178.16/issuetoc